Enhancing Academic Performance in Agricultural Sciences: The Impact of Inquiry-Based Learning on Learners - Mbhanyisi, Perfect; Ncisana, lusanda; Mashishi, Malesela; Masha, Mmapake Florence; Buthelezi, Michael Mbhongiseni (Research in Social Sciences and Technology, 2025)
The Curriculum Assessment Policy Statement document indicates that Animal Studies comprise a substantial part of the Grade 12 syllabus, more so than topics like soil science, agro-ecology, agricultural economics, and crop science. This highlights the importance of exploring diverse teaching approaches in the beginning of Grade 10, as a strong foundation in earlier grades could improve understanding of Animal Studies in Grade 12. This study explored the effectiveness of inquiry-based learning (IBL) in teaching Grade 10 learners about poultry breeds. A mixed-method approach was used to compare IBL with traditional teaching methods. Forty-six Agricultural Sciences learners were randomly assigned to a quasi-experiment, with 23 learners in the experimental group taught through IBL and 23 in the control group taught using the traditional lecture method (TLM). Both groups underwent pre- and post-performance tests. The quantitative data were analysed using an independent t-test, while qualitative data were thematically analysed through document analysis of the learners' assessment scripts. Results from the t-test indicated that the experimental group achieved significantly higher mean scores than the control group (p<0.05). Furthermore, the document analysis revealed that IBL fosters higher-order thinking, active participation, and critical thinking skills. Consequently, the inquiry-based learning approach proves to be an effective tool for enhancing learners’ academic performance. These findings suggest that educators and policymakers should consider integrating inquiry-based learning strategies into the teaching of Agricultural Sciences curriculum to improve achievement of academic outcomes. Emphasis on active engagement and critical thinking can lead to more meaningful learning experiences for learners.